Job satisfaction based on organizational support, organizational culture and work environment - Dharma, Edy; Efendi, Efendi; Sherly, Sherly (Junal Ilmu Manajemen, 2025)
Finding out how organizational support, organizational culture, and work environment impact worker job satisfaction at the Office of the Pematangsiantar Regional Financial Management Agency is the aim of this study. This study uses a literature investigation design and field investigation. The populace in this study is 89 workforce at the Office of the Pematangsiantar Regional Financial Management Agency. Both qualitative and quantitative data were employed in this investigation. Both primary and secondary data sources were employed. Questionnaires, interviews, and documentation were used to gather data. The data was analyzed by PLS, where involved the evaluation of the outer model and the inner model. The outcomes of this study can be ended as follows: (1) Job satisfaction is favorably and strongly connected with organizational culture; (2) job satisfaction and organizational culture have a positive and meaningful influence on each other; and (3) job satisfaction is positively and considerably impacted by organizational culture. The results of this study imply that fostering a positive organizational culture can significantly enhance job satisfaction, suggesting that the Pematangsiantar Regional Financial Management Agency should prioritize cultural development to improve employee morale and performance. For further research, it would be beneficial to explore additional variables such as leadership style or employee engagement to provide a more comprehensive understanding of factors influencing job satisfaction.